Comparison of the calcium-related factors in Parkinson’s disease patients with healthy individuals - Sadra Samavarchi Tehrani; Mohammad Sarfi; Tooba Yousefi; Alijan Ahmadi Ahangar; Hemmat Gholinia; Reza Mohseni Ahangar; Mahmoud Maniati; Payam Saadat (Caspian Journal of Internal Medicine, 2020)
Background: Parkinson’s disease (PD) is one of the most common neurodegenerative diseases (ND). Studies have demonstrated that biochemical markers have an association with PD. We aimed to investigate an association of biochemical markers including calcium, vitamin D, alkaline phosphatase (ALP), parathormone (PTH), and phosphorous with PD. Methods: This study was conducted on 139 PD patients and 100 healthy individuals. Serum levels of calcium, phosphorous, ALP, PTH and vitamin D were evaluated. Furthermore, student’s t-test and logistic regression models were used by SPSS. Results: The mean levels of calcium (9.4±0.7 and 9.0±0.8 ) and vitamin D (29.7±22.1 and 25.8±23.7) were higher in PD patients as compared with healthy controls, which only status of calcium being significantly different in the two groups (P<0.001). Levels of ALP (202.4±96.7 and 242.9±142.4) and phosphorous (3.6±0.6 and 4.22±1.1) were significantly different comparing PD patients with healthy subjects (P<0.01, P<0.001, respectively). ALP and phosphorous were significantly different in the two groups (OR=0.996, [CI 95%, 0.994-0.999], P <0.001, OR= 0.475, [CI 95%, 0.325-0.694], P<0.001, respectively). Furthermore, increased levels of calcium resulted in an elevated risk of PD (OR= 2.175, [CI 95% 1.377-3.435], P <0.001). Conclusion: Results show that mean levels of calcium are higher in PD patients relative to healthy controls. Thereby, higher levels of calcium may be associated with PD.